The Burden of Hepatitis C Virus Infection Is Growing: A Canadian Population-Based Study of Hospitalizations from 1994 to 2004 - Robert P Myers; MingFu Liu; Abdel Aziz M Shaheen (Canadian Journal of Gastroenterology)
BACKGROUND: Nearly 1% of Canadians are infected with the hepatitis C virus (HCV). Simulation analyses have suggested that HCV will place an increasing burden on the health care system as the infected population ages, but supportive clinical data are limited.